Teleneuropsychology for vascular cognitive impairment: Which tools do we have? - Emilia Salvadori; Leonardo Pantoni (Cerebral Circulation - Cognition and Behavior, 2023)
The halt of clinical activities imposed during the COVID-19 pandemic forced clinicians to find alternative strategies to provide continuity of care and services, and led to a renewed interest in use of teleneuropsychology (TNP) to remotely assess patients. Recent TNP guidelines recommend maximizing the reproduction of standard in-person assessment, particularly through videoconferences. However, consistency of the adaptations of usual cognitive tests to videoconference needs further elucidation.This review aims at critical reviewing which cognitive tests could be recommended for a remote evaluation of patients with vascular cognitive impairment (VCI) among those widely recognized as reference standards.Current evidence supports the use of global cognitive efficiency (MMSE and MoCA), verbal memory (Revised Hopkins Verbal Learning Test), and language tests (phonemic and semantic verbal fluencies, Boston Naming Test), while there is a lack of strong validity support for measures of visuospatial functions (Rey-Osterreith Complex Figure), and executive functioning and processing speed (Trail making Test, and Digit symbol or Symbol digit tests). This represents a major limitation in the evaluation of VCI because its cognitive profile in often characterized by attention and executive deficits.At present, a videoconference TNP visit appears useful for a brief evaluation of global cognitive efficiency, and to ‘triage’ patients towards a second level in person evaluation. In future, hybrid models of TNP based on data collected across multiple modalities, incorporating both adaptation of usual cognitive tools and new computerized tools in the supervised videoconference setting, are likely to become the best option for a comprehensive remote cognitive assessment.